Progressive Hydrocephalus: Symptoms and Signs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The etiologies and clinical features of progressive hydrocephalus in 107 children, 56 with and 51 without shunts, were analyzed retrospectively at the Department of Neurology, Royal Hospital for Sick Children, Edinburgh, Scotland.